Formulation and Characterization of Nanoemulsion from Traditional Extracts for Antidiabetic - Dzaki Fikri Firdaus Bakri; Muhtadi Muhtadi; Erindyah Retno Wikantyasning (GLOBAL HEALTH SCIENCE GROUP, 2023)
Diabetes is a degenerative disease with the highest number of sufferers in the world. Traditional medicine naturally uses extracts of plants and animals in great demand. Curse fish or snakehead fish (Channa striata), elephant lempuyang (Zingiber zerumbet L) and rambutan rind (Nephelium lappaceum) are proven to have active ingredients of albumin, quercetin and geraniin as anti-diabetics. Disadvantages of these active compounds, namely having low solubility, permeability and stability, causing a decrease in bioavailability. Self Nano Emulsifying Drug Delivery System (SNEDDS) is a form of nanoemulsion and is a solution for delivering active compounds to increase permeability, stability and solubility of active compounds. The formula was made using olive oil as the oil phase, PEG 400 as the cosurfactant, span 80, tween 20 and tween 80 as the surfactant. The research aims to obtain the optimum nanoemulsion formula using the HLB method. Percent transmittance and emulsification time are used to determine the optimum formula. The selected formula was further tested with a particle size analyzer, zeta potential, PDI. Based on the 30 formulas that were made, F9 was the chosen formula with an HLB value of 15 with the oil, surfactant, cosurfactant phases at a ratio of 8:1:1. Formula F9 has an emulsification time of 18.76 seconds, a transmittance of 97.8%. The particle size test results were 196.2 nm and -30.1 zeta potential values. The research results showed that SNEDDS preparations were able to form nanoemulsions spontaneously and had good characteristics.